WORDS FOR SCENT AND FRAGRANCE IN THE TALE OF KIEU - Nguyễn Thị Quốc Minh (Tạp chí Khoa học Đại học Đà Lạt)
Words for scent and fragrance appear in more abundance in “The Tale of Kieu” than in any other classical Vietnamese literary work. However, scent, aroma, smell, and fragrance are quite different. There are things and people who have a fragrance without a smell and vice versa. The expressive meanings of scent are very different and are expressed according to different aesthetic ideals and artistic principles. This article gives an in-depth exploration and understanding into such matters. This is also a way to discover and assert that Nguyen Du was an artistic genius.